Penerapan Terapi Bermain dalam Mengatasi Perilaku Anak Hiperaktif di TK Negeri Pertiwi Banyorang Kabupaten Bantaeng - Arsyad, Andi Indri (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2025)
Play therapy is one form of therapy used to overcome hyperactive child behavior. This research uses descriptive qualitative research, which is located at Pertiwi Banyorang State Kindergarten, Bantaeng Regency using a psychotherapy approach. Primary data sources in this study are therapists as key informants and additional informants, namely the principal, parents of students and two hyperactive children. While secondary data sources are books, reports, journals, and other data sources as a complement. The data collection methods used are observation, interviews and documentation. Data processing and analysis techniques are carried out through three stages, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that there are two forms of application of play therapy in overcoming hyperactive children’s behavior at Pertiwi Banyorang State Kindergarten, Bantaeng Regency, namely constructive play therapy and sensorimotor play therapy. The benefits of the application of play therapy in overcoming hyperactive children’s behavior at Pertiwi Banyorang State Kindergarten, Bantaeng Regency are: children become calmer and more controlled, increased concentration, children feel valued and cared for and children’s health is controlled.